Pembacaan Heuristik dan Hermeneutik pada Puisi-Puisi Cinta Karya W.S. Rendra - Rohadatul Afifah; Kaswadi; Rini Damayanti (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The purpose of this study was to describe the heuristic and hermeneutic readings in WS's Poems of Love. Rendra. The method used in this research is qualitative with a descriptive approach and a semiotic approach. Sources of data discussed in this study are WS Rendra's poems, namely: Permintaan, Kami Berdua, Tempramen, Kepada Awan Lewat, Telah satu, Optimisme, Ayam Jantan, Janganlah Jauh, Surat Seorang Istri, dan Barangkali Karena Bulan.. The results of the analysis discussed in this study are that there are themes of love. These poems tell a youth that is so simple, adult poetry that feels deep and serious in the journey of love, and old age poems in the form of gratitude for the proven blessings of true love.